(3GdJYQja HeG CfSJ GdgLQI ef eYGde GdgLQIs - (3CHh YHO Gddg eMeO Hf CMeO Hf Nda LeGd GdOjf GdNRQLj GdYHGOi GdeYQha HGdeWQis; (3GHf GdfLGQ , eMeO Hf eMehO Hf GdMSf Hf gHI Gddg Hf eMGSf, eMH GdOjf CHh YHO Gddg,J (B643 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi TQa WjHI GdWjHI HMdhd eUWaGg s
(3BNQgG (B:s
(3GdMeO ddg QH GdYdejf hUdhGJg hSdGeg Ydi SjOfG eMeO hBdg hUMHg s
(3bQFJ Ydi YOI YdeGA hYdjgG SeGYGJs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B86 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B317s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B95 s
Keywords: (3GdJGQjNs